2023
DOI: 10.1021/acs.est.2c07481
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Tides and Environmental Injustice: Social Vulnerability to Sea Level Rise and Flooding of Hazardous Sites in Coastal California

Abstract: Sea level rise (SLR) and heavy precipitation events are increasing the frequency and extent of coastal flooding, which can trigger releases of toxic chemicals from hazardous sites, many of which are in low-income communities of color. We used regression models to estimate the association between facility flood risk and social vulnerability indicators in low-lying block groups in California. We applied dasymetric mapping techniques to refine facility boundaries and population estimates and probabilistic SLR pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…Further analysis of our results showed that the average increase in treatment capacity required to accommodate projected runoff changes was 21%, which will increase capital costs for their construction accordingly. Such investment decisions also provide an opportunity to take into account the environmental justice implications of the disproportionate impact that projected climate change impacts are likely to have on socially underserved communities 76 .…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of our results showed that the average increase in treatment capacity required to accommodate projected runoff changes was 21%, which will increase capital costs for their construction accordingly. Such investment decisions also provide an opportunity to take into account the environmental justice implications of the disproportionate impact that projected climate change impacts are likely to have on socially underserved communities 76 .…”
Section: Discussionmentioning
confidence: 99%
“…Sea level rise will flood toxic waste sites, cesspools and septic systems, municipal dumps, and polluted groundwater. In many cases, communities of color will be first to experience health impacts ( 123 ).…”
Section: Oceansmentioning
confidence: 99%
“…It has also been reported that the specific geographic conditions may impact the risk of coastal floods, such as the coastal geomorphology and coast types [5,6]. A number of studies have predicted that coastal flooding will continue to be one of the main risks for worldwide coastal environmental security, with increasing intensity (e.g., [7][8][9][10][11]).…”
Section: Introductionmentioning
confidence: 99%